Volume 3: 6th Design for Manufacturing Conference 2001
DOI: 10.1115/detc2001/dfm-21194
|View full text |Cite
|
Sign up to set email alerts
|

Assembly Quality Methodolgy: An Application of the Defect Prediction to Audio Equipment Assembled at Various Manufacturing Sites

Abstract: This paper describes the development of the quantitative predictor of defects that works not only on the whole product but also on its modular units. The authors divide the assembly process of a product into small modules, and apply the Assembly Quality Methodology (AQM) to determine the assembly complexity of the modules. The authors also verify the correlation between complexity factor of the modules and their defect rates. The newly proposed floating threshold assembly time improves the correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…According to Swain and Guttmann [18], human errors can be defined as "any member of a set of human actions that exceed some limit of acceptability, i.e., an out-of-tolerance action, where the limits of tolerable performance are defined by the system." It has been acknowledged that assembly errors are one of the main causes of defects in manufacturing systems [14,[19][20][21][22]. For example, in research conducted at Fuji Xerox China, it was found that 20% of the total defects in copier assembly were caused by operator errors [19].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Swain and Guttmann [18], human errors can be defined as "any member of a set of human actions that exceed some limit of acceptability, i.e., an out-of-tolerance action, where the limits of tolerable performance are defined by the system." It has been acknowledged that assembly errors are one of the main causes of defects in manufacturing systems [14,[19][20][21][22]. For example, in research conducted at Fuji Xerox China, it was found that 20% of the total defects in copier assembly were caused by operator errors [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in research conducted at Fuji Xerox China, it was found that 20% of the total defects in copier assembly were caused by operator errors [19]. Similarly, data from a production facility of audio equipment in Japan showed that defects in manual assembly processes represented 17% of total defects [20]. In the case of car manufacturing, in a study conducted at a Volvo plant in Sweden, researchers analyzed the quality outcomes of a production volume of 47061 cars and found several errors in the assembly process, such as incorrectly installed parts, incorrect torque applied to components, missing bolts and clips, scratches and dirt on components, and insufficiently tightened cables or pipes [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…With this consideration in mind, Hinckley (1993) found that defect per unit (DPU) was positively correlated with total assembly time and negatively correlated with number of assembly operations. Moreover, Shibata et al (2001) developed a quantitative predictor that worked not only on the whole product but also on its modular units. In this method, the newly proposed floating threshold assembly time improved the correlation between complexity factor and DPU.…”
Section: Previous Workmentioning
confidence: 99%
“…The process-based complexity factor is derived from a time standard defined for a set of assembly tasks. Initially proposed by [Hinckley, 1998] and utilized by [Shibata et al, 2001], [Shibata, 2002], [Shibata et al, 2003a,b] and [Su et al, 2009] the process complexity factor (Cf P ) shows satisfactory correlation with defect rates and is defined as:…”
Section: Process-based Complexity Factormentioning
confidence: 99%
“…Research by [Shibata et al, 2001[Shibata et al, , 2003a, [Hinckley, 1998] and recently [Su et al, 2009] report a strong co-relation between the complexity factors (product and process) and Defects per Unit (DPU). These case studies focus on data of processes that had already reached a steady state.…”
Section: Steady-state Defects Per Unitmentioning
confidence: 99%